Dinamika Psikologis Keluarga Poligami Penyandang Tuna Netra - Pascayani, Ainulhusnah (Universitas Negeri Makassar, 2017)
This research was held to find out the dynamics of psychological subject in polygamy, the way of handle the family, and the interaction of another family member, the research method is qualitative research by using study case approach through deepÂ interview and observation during the interview, the subject of the research is the main subject it is husband, for another subjects are first wife, second wife, third wife, and forth wife, and one of the children from the main subject, the research result shows that there is psychological dynamic in her polygamy life and her family, the are, positive impact and negative impact, from the positive impact like protect and help the old women but not yet marriage and the woman who have criminal problem like harassment in their family, stay away from something not good in religion, and can built a good relationship, the wife have a partner in working and care together to the husband, and feel free when they donâ€™t have time, the other ones, there is a negative impact, there are there is a jealousy between the wife and the polygamy, the is negative thinking in social life, the way of subject care the family, by teaching religious point to all the member of family, the interaction of family member held by meet together, built a relationship, care each others, protect, and keep to all the member of family, the subject is blind person but he has a good personality to all people so thatâ€™s why many woman love her.